2003
DOI: 10.1002/ar.a.10036
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of vitamin A‐storing lipid droplets in hepatic stellate cells in liver lobules—A comparative study

Abstract: To investigate the storage mechanisms of vitamin A, we examined the liver of adult polar bears and arctic foxes, which physiologically store a large amount of vitamin A, by high-performance liquid chromatography (HPLC), transmission electron microscopy (TEM) morphometry, gold chloride staining, fluorescence microscopy for the detection of autofluorescence of vitamin A, staining with hematoxylin-eosin (H&E), Masson's trichrome, and Ishii and Ishii's silver impregnation. HPLC revealed that the polar bears and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 32 publications
2
31
0
1
Order By: Relevance
“…It was previously reported that the liver lobule physiologically shows zonal heterogeneity in terms of vitamin A storage (Wake and Sato, 1993;Zou et al, 1998;Higashi and Senoo, 2003). In our present study, this heterogeneity of vitamin A storage disappeared during liver regeneration and did not return to normal by 14 days after PHx, at which time the liver volume generally does return to normal (Michalopoulos and DeFrances, 1997).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…It was previously reported that the liver lobule physiologically shows zonal heterogeneity in terms of vitamin A storage (Wake and Sato, 1993;Zou et al, 1998;Higashi and Senoo, 2003). In our present study, this heterogeneity of vitamin A storage disappeared during liver regeneration and did not return to normal by 14 days after PHx, at which time the liver volume generally does return to normal (Michalopoulos and DeFrances, 1997).…”
Section: Discussionsupporting
confidence: 48%
“…These cells also play a pivotal role in the regulation of vitamin A homeostasis (Senoo and Wake, 1985;Blomhoff et al, 1990;Senoo et al, 1990Senoo et al, , 1993aSenoo et al, , 1993bBlomhoff and Wake, 1991;Imai et al, 2000b). Earlier we reported the existence of a gradient of vitamin A-storing capacity in the liver and found that it was not dependent on the vitamin A amount in the organ (Higashi and Senoo, 2003). This gradient was expressed as a symmetrical biphasic distribution starting at the periportal zone, peaking at the middle zone, and sloping down toward the central zone in the liver lobule.…”
mentioning
confidence: 93%
“…HSCs are heterogenous with regard to the vitamin A content. [27][28][29][30][31] However, the functional significance of this heterogeneity is unclear. It is possible that our isolation procedure to prepare HSC could result in the selection of cells with higher vitamin A content.…”
Section: Generation Of Transgenic Mice and Genotypingmentioning
confidence: 99%
“…All HSCs in hepatic parenchyma have a similar function but are heterogeneous in desmin expression, vitamin A storage, proliferative activity, cytokine production, and ECM production (Blomhoff and Wake, 1991;Greenwel et al, 1993;Zou et al, 1998;Higashi and Senoo, 2003). The activated HSCs in culture show myofibroblast-like cell shapes with well-developed stress fibers of actin cytoskeleton.…”
Section: Characteristics Of Gene Expression Including Cytoskeleton Prmentioning
confidence: 99%